Environmental Awareness and Social Empathy as Predictors of Ecological Citizenship among Generation Alpha - Rahmawan, Alfian Arsa; Patmisari, P (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to determine the influence of environmental awareness and social concern on the ecological citizenship of Generation Alpha students in Kartasura District.Methodology: The research used a quantitative descriptive method with a correlational design. The sampling technique used was proportional random sampling. The research population consisted of 4,183 junior high school and MTs students, with a sample of 255 respondents.Results: The results show that environmental awareness has a positive and significant effect on students' ecological citizenship, as evidenced by a Sig. value of < 0.001 (< 0.05) and a T-count of 7.296 > T-table 1.969, meaning that H0 is rejected and H1 is accepted. Conversely, social concern does not have a significant effect on ecological citizenship, as indicated by a Sig. value of 0.138 (> 0.05) and a T-count of 1.489 < T-table 1.969, so that H0 is accepted and H2 is rejected. These findings show that social concern does not always lead to ecological behavior. Simultaneously, environmental awareness and social concern have a significant effect on ecological citizenship, based on a Sig. value of 0.001 (< 0.05) and an F-count of 56.363 > F-table 3.031, meaning that H0 is rejected and H3 is accepted, which means that both independent variables have a combined effect on ecological citizenship.Applications/Originality/Value: This study highlights the key role of environmental awareness in shaping Generation Alpha's ecological citizenship and offers practical guidance for schools, given that social concern does not always translate into ecological action.